Integration of Islam and Mathematics: Religious and Mathematics Education In Grand Mosque of West Sumatra - M. Imamuddin; Isnaniah Isnaniah (AL-ISHLAH: Jurnal Pendidikan, 2024)
The study aimed to determine the integration of religion and mathematics education within the context of the Grand Mosque of West Sumatra, with a specific focus on its potential impact on mathematics learning. The study was undertaken at the Grand Mosque of West Sumatra. The research methodology employed in this study is descriptive qualitative research utilising an ethnographic approach. Data gathering methods include literature review, direct observation, documentation analysis, and conducting interviews. Data analysis techniques include data reduction, data presentation, and conclusion. The findings of this study indicate that the Grand Mosque serves as a multifaceted institution encompassing several functions such as a place of worship, a platform for preaching, an educational hub, a centre for character development, a catalyst for moral and social advancement, a hub for economic empowerment, and a destination for religious tourism. The Grand Mosque serves as a conducive environment for the acquisition of mathematical knowledge due to the presence of several mathematical principles embedded within the worship activities, as well as within the physical structure and courtyard of the Mosque. The Grand Mosque incorporates mathematical ideas such as multipli-cation, parallel lines, straight lines, curves, triangles, rhombuses, rectangles, trapezoids, congruence, and social arithmetic. According to the data above, it can be inferred that the West Sumatra Grand Mosque serves as a venue for religious and mathematical education. Consequently, this establishment holds potential as a resource for students to acquire knowledge in religious studies and develop a comprehensive understanding of mathematical principles.